Inhibitory effects of ginkgolides on nitric oxide production in neonatal rat microglia in vitro. - Du Ze-Ying; Li Xiao-Yu (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of ginkgolide A (GA) and B (GB), apafant (Apa), and N omega-nitro-L-arginine (L-NA) on nitric oxide (NO) production in cultured neonatal rat microglia. METHODS: NO concentration was represented by nitrite which was determined by Griess reaction. RESULTS: In resting microglia, no inhibitory effects of GA, GB, and Apa were observed. L-NA inhibited NO production, its IC50 value (95% confidence limits) being 3.4 (0.8-14.9) mumol.L-1. GA, GB, and L-NA inhibited NO production in LPS-stimulated microglia, and their IC50 values (95% confidence limits) were 5.7 (1.8-18.1), 1.1 (0.3-4.4), and 0.5 (0.1-2.8) mumol.L-1, respectively. Apa did not inhibit NO production. CONCLUSION: GA and GB inhibited NO production in LPS-stimulated microglia.